Application of High-Resolution Flat Detector Computed Tomography in Stent Implantation for Intracranial Atherosclerotic Stenosis - Li, Tengfei; Wang, Yuting; Ma, Ji; Levitt, Michael; Mossa-Basha, Mahmud; Shi, Chengcheng; Ran, Yuncai; Ren, Jianzhuang; Han, Xinwei; Zhu, Chengcheng (Frontiers in Neuroscience, 2021)
Objective: To evaluate the utility of high-resolution flat detector CT (HR-FDCT) compared to traditional flat detector CT (FDCT) for stent placement in symptomatic intracranial atherosclerotic stenosis (ICAS). Methods: We retrospectively reviewed the clinical data of 116 patients with symptomatic ICAS who underwent stent implantation. Images were acquired using conventional FDCT (voxel size 0.43 mm isotropic) and HR-FDCT (voxel size 0.15 mm isotropic). Immediately after stent deployment, dual volume 3D fusion images were obtained from 3D-digital subtraction angiography (DSA) and HR-FDCT. The image quality for stent visualization was graded from 0-2 (0:not able to assess, 1:limited, but able to assess; 2:clear visualization), and the stent expansion status (full, under-expanded or poor apposition) was also recorded. Results: 116 patients with symptomatic ICAS were successfully treated using 116 stents (58 Neuroform EZ, 42 Enterprise, and 16 Apollo). Mean pre-stent stenosis was 80.5±6.4%, which improved to 20.8±6.9% after stenting. Compared to FDCT, HR-FDCT improved visualization of fine structures of the stent that significantly improved the image quality (mean score: 1.63±0.60 vs. 0.41±0.59, P<0.001). In 19 patients, stent under-expansion (N=11) or poor apposition (N=8) was identified by HR-FDCT but not by conventional FDCT. After balloon dilatation, stent mal-apposition was shown to have improved on HR-FDCT. None of the 19 patients with stent mal-apposition experienced near-term complications during hospitalization or had in-stent stenosis at 6-months follow-up.